Effect of Combination of Media Cultivation and Varieties Against Against Plant Growth and Yield of Tomato (Lycopersicum esculentum Mill) By Hydroponic Substrates - Mega Marzarina; Mardiah Hayati; Elly Kesumawati (Jurnal Ilmiah Mahasiswa Pertanian, 2016)
Effect of Combination and Varieties Growing Media on the Growth and Crop Tomato (Lycopersicum esculentum Mill) in hydroponic substrate. This study aims to determine the best combination and variety of growing media on growth and yield of tomato plants in hydroponic substrate. Research conducted at the Experimental Farm, Faculty of Agriculture, University of Syiah Kuala, which lasted from January to May 2014. This study used a randomized block design 3 x 3 factorial design with three replications. This study consisted of two factors, the first factor is the combination of growing media consisting of a combination of sand + rice husk, sand + sawdust, sand + coconut coir. The second factor is composed of tomato varieties Hybrid varieties (Peto-seed), Superior (Ratna) and Local (Ground). Parameters measured were plant height and trunk diameter respectively at 15, 30, and 45 days after plant (HST), the number of flower planting age of 60, 67, 74, 81 and 88 days after planting, as well as the number of total fruit and total weight of the fruit planting. The results showed that growing media very significant effect on the diameter of the stem ages of 15 and 30 DAT, the number of flower planting age of 60, 67, 74, 81 and 88 days after planting, the number of total fruit crop and the weight of total fruit crop, significantly affected plant height age 15 and 30 DAT, and diameter at base age 45 HST. But no real effect on the plant height age of 45 HST. The growth and yield of tomato plants best seen in medium sand + husk. Varieties very significant effect on the amount of interest the age of 67 and 81 days after planting, the total number of fruit crops and fruit weight total crop. But no real effect on plant height and diameter at base age of 15, 30 and 45 days after planting. Growth and yield of tomato plants best seen in hybrid varieties (Peto-sedd). There is a very real interaction between the growing media and varieties of the total number of fruit crops and no real effect on other variables. Best interaction that combined treatment of the planting medium sand + rice husk and hybrid varieties (Peto-sedd).Keywords: tomatoes, Growing Media, varieties, hydroponic substrate.